PENGARUH KELELAHAN KERJA, KESEIMBANGAN KEHIDUPAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA (STUDI KASUS PADA KARYAWAN OPERATOR SPBU PERTAMINA 34-1512 SERPONG TANGERANG SELATAN) - Annisa Tri Agustina (2023)
This research is a quantitative research with the aim of knowing the effect of burnout, work-life balance, work environment on job satisfaction. The total population is 43 and the sample is 43 operator employees of SPBU Pertamina 34-15312 Serpong South Tangerang. The analysis technique use quantitative data analysis using Partial Least Square (PLS). The result of this study indicate (1) burnout has a positive and significant effect on job satisfaction, (2) work-life balance has a positive and significant effect on job satisfaction, (3) work environment has a positive and significant effect on job satisfaction, (4) burnout, work-life balance, work environment simultaneously have a positive effect on job satisfaction.